Instagram Content Analysis on @kualanamu.airport Account as Company Branding Media - Rangkuti, Ismaliyah Yusuf; Setianti, Yanti; Warta, Waska (Komunika, 2024)
Kualanamu International Airport Deli Serdang utilizes Instagram social media as the main media in disseminating information and education related to airports and flights to the public consistently. in disseminating information and education related to airports and flights to the public consistently and periodically through Instagram. and periodically through account @kualanamu.airport. The utilization of social media is carried out as a branding effort the company to the public. So the author focuses on this analysis on the Instagram content presented by the @kualanamu.airport account which aims to find out the content classification and follower algorithm in accessing the content provided. content provided. This research uses qualitative methods of non-participant observation and literature study. The results of the analysis found entertainment, education, collaboration, and information content during the observation period of the @kualanamu.airport account, Kualanamu Airport Public Relations through this account is considered successful in shaping brand awareness to the public. brand awareness to the public, thus increasing public satisfaction and public understanding in using air transportation. However, the infographics displayed on information content on @kualanamu.airport are not all equipped with easily recognizable thumbnails. that are easily recognizable.